1981
DOI: 10.1159/000123146
|View full text |Cite
|
Sign up to set email alerts
|

Adenohypophysis Has an Inherent Property for Pulsatile Prolactin Secretion

Abstract: Hypophysectomized male rats with adenohypophyses grafted under the kidney capsule (HG rat) for 3 weeks with or without estradiol implantation, were used to examine prolactin (PRL) secretion independent of hypothalamic influence. Changes in the circulating PRL concentration were monitored by taking blood samples every 2 min via an indwelling atrial cannula. The circulating PRL concentration did not remain at a constant level but fluctuated with time. When estradiol (100 µg/kg) was administered to HG rats throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 18 publications
4
22
0
Order By: Relevance
“…Based on critical revaluation of older data and jetlag studies, Van Cauter and coworkers [15,16] suggested that human prolactin is not entirely entrained with sleep. A study in rats also showed that an intrinsic periodicity in prolactin secretion can be found in transplanted pituitaries [17]. In our patients who were kept under a constant day-light schedule, a nocturnal surge of prolactin was present, although with reduced amplitude, for months after total disruption of the physiological sleep activity.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Based on critical revaluation of older data and jetlag studies, Van Cauter and coworkers [15,16] suggested that human prolactin is not entirely entrained with sleep. A study in rats also showed that an intrinsic periodicity in prolactin secretion can be found in transplanted pituitaries [17]. In our patients who were kept under a constant day-light schedule, a nocturnal surge of prolactin was present, although with reduced amplitude, for months after total disruption of the physiological sleep activity.…”
Section: Discussionsupporting
confidence: 69%
“…Among the others, prolactin and somatotropin have long been known to show episodic peaks of secretion superimposed upon a significant 24-hour rhythm mainly determined by a distinct nocturnal elevation [1][2][3][4][5][6][7][8][9][10][11][12][13][14], Data from the literature clearly point to a relation of the nocturnal surge of somatotropin to the onset of sleep [4][5][6][7][8][9][10][11][12][13][14], The nocturnal rise of prolactin occurs in later hours and has also been shown to shift with the sleep period [1][2][3]. However, the sleep entrainment of the nocturnal prolactin surge has been questioned both in humans [15,16] and in rats [17].…”
Section: Introductionmentioning
confidence: 99%
“…Another consideration that some prolactin pulses may be generated semiautonomously within the pituitary gland by as yet incompletely characterized mechanisms, is suggested by studies of perifused or transplanted pituitary glands (21,22). However, precisely how such intraglandular-triggered prolactin secretory bursts could be coupled to LH release episodes is not clear.…”
Section: Figmentioning
confidence: 99%
“…Most of the prolactin present in the cir culation under these circumstances should be derived from the ectopic gland [24] which is not under the tonic hypothalamic inhibition, so that an increased secretion rate of prolactin from these cells might by responsible for increased circulating levels of the hormone. This suggests that the pulsatile pattern of peripheral prolactin in pitu itary-grafted rats is due to the persistence of the secretory pulsatile behavior of the lactotrophs in the ectopic gland [19]. The increase in the number of lactotrophs in the ectopic gland might also account for the higher mean val ues of the hormone during the studied period, and the number of these cells increased immediately after pitu itary grafting [25], Administration of CyA to sham-operated rats induced alterations in the pulsatile pattern of prolactin release which resemble the effects of pituitary grafting: dimin ished frequency, increased amplitude and duration of the peaks.…”
Section: Discussionmentioning
confidence: 98%
“…One of them may originate in the hypothala mus, and depend on dopaminergic activity [18] and the other is present in the pituitary and depends on the inher ent pulsatile property of the lactotrophs [19].…”
Section: Discussionmentioning
confidence: 99%